EFEKTIVITAS E-MODULE BERBASIS REFUTATION TEXT UNTUK MEREMEDIASI MISKONSEPSI - Islami, Fadhilah Hidayati; Silitonga, Haratua Tiur Maria; Hamdani, Hamdani (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
This study aims to describe the effectiveness of using refutation text-based e-modules to remediate misconceptions about dynamic electricity at SMP Negeri 2 Sungai Raya. Effectiveness is seen from changes in the number of students' misconceptions before and after the use of refutation text-based e-modules. The research method used in this study was a Pre-Experimental Design with a one-group pretest-posttest design. The research subjects consisted of 58 class IX students. Data were collected using a two-tier multiple-choice reasoning diagnostic test. Data analysis used the SPSS-assisted McNemar test to see changes in the number of students' misconceptions before and after using refutation text-based e-modules. Based on the results of the MC Nemar test analysis with the help of SPSS, each item indicator obtained a significant value. It can be concluded that there is a change in the number of students' misconceptions before and after using refutation text-based e-module. This shows that an e-module based on refutation text is effective in reducing the number of students who experience misconceptions. Thus, e-module based on refutation text can be used as teaching material for educators to reduce students' misconceptions.